Colorimetric and turn-on fluorescence determination of mercury (II) by using carbon dots and gold nanoparticles. (25th January 2021) - Lu, Changfang; Ding, Hao; Wang, Yutong; Xiong, Chaoying; Wang, Xianxiang
Abstract: A colorimetric and turn-on fluorometric assay with high sensitivity and selectivity is described for the optical detection of mercury (II) ions (Hg 2+ ), based on carbon dots with –SH (SN-CDs) and gold nanoparticles (AuNPs). On addition of Hg 2+, the color of the system (SN-CDs/AuNPs) changes from red to blue. A new absorption peak appears at 700 nm, and its absorbance increases with the concentration of Hg 2+, while at 530 nm, the absorbance of AuNPs decreases. Taking the ratio of absorbance at 700 and 530 nm as a signal, a colorimetric method with linear detection range of 0.5–4.0 μ M was established for the determination of Hg 2+ . Meanwhile, citrate ions on the surface of AuNPs can reduce Hg 2+ to Hg 0, and through the strong affinity of Hg 0 and gold, gold–mercury alloys were formed to occupy the surface of AuNPs, so that the SN-CDs were re-free and the fluorescence of SN-CDs was restored. Consequently, a fluorometric method was founded in the linear detection range from 0.5 to 15.0 μ M of mercury (II). This dual-mode (colorimetric and turn-on fluorometric) method was applied successfully for determination of Hg 2+ in real water samples.